Impact of Tobacco and Smoking on Oral Health - Ali Tahir, Ashar Hussain, Wajeeha Jabeen, Hafiz Mahmood Azam, Ali Anwer, Resham Hafeez (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tobacco use, both in smoking and smokeless forms, poses a significant threat to oral health, contributing to conditions such as periodontal disease, dental caries, oral mucosal lesions, and altered salivary function. Despite extensive public health campaigns, tobacco consumption remains prevalent, especially in developing countries, leading to a persistent oral disease burden. Objective: To assess and compare the impact of tobacco use—including smoking and smokeless tobacco—on periodontal health, dental caries, oral mucosal lesions, salivary pH, and oral hygiene behavior among adult patients. Methodology: An analytical cross-sectional study was conducted over 12 months at tertiary care dental institutions following STROBE guidelines. A total of 1,200 participants aged 18–65 years were recruited using stratified random sampling, comprising 600 tobacco users (450 smokers and 150 smokeless tobacco users) and 600 age- and gender-matched nonsmokers. Data collection included self-reported questionnaires and clinical oral examinations assessing Community Periodontal Index (CPI), DMFT index, presence of mucosal lesions, salivary pH and flow rate, and oral hygiene behaviors. Examiners were calibrated (κ = 0.89), and all data were analyzed using SPSS version 26.0. Logistic regression was used to identify odds ratios (OR) for poor oral outcomes, adjusting for confounders. A p-value < 0.05 was considered significant. Results: Smokers demonstrated the highest prevalence of periodontal disease (45% periodontitis), mucosal lesions (15% smoker’s melanosis), and DMFT scores (4.2 decayed teeth). Salivary pH and flow rate were significantly lower in smokers (pH: 6.3 ± 0.4; flow: 0.8 mL/min) compared to nonsmokers. Oral hygiene behaviors were significantly poorer among tobacco users, with only 28% of smokers brushing twice daily. Logistic regression revealed increased odds of periodontal disease (OR: 3.5, CI: 2.8–4.4), dental caries (OR: 2.8, CI: 2.1–3.6), and mucosal lesions (OR: 5.4, CI: 3.9–7.2) among smokers. Smokeless tobacco users also showed elevated risks but to a lesser degree. Conclusion: Tobacco use, particularly smoking, significantly impairs oral health by increasing the risk of periodontal disease, caries, and mucosal lesions, while also reducing salivary protection and promoting poor oral hygiene behaviors. These findings emphasize the critical need for targeted tobacco cessation programs integrated with dental care to mitigate oral disease risk. Keywords: Tobacco Use, Smoking and Oral Health, Periodontal Disease, Oral Mucosal Lesions, Dental Caries